Aktivitas Antibakteri Secara In-Vitro Ekstrak Metanol Excoecaria cochinchinensis Lour dan Kombinasinya dengan Obat Komersial - Nurhasana, Devi; Febriansyah, Rahmaga; Avidlyandi, Avidlyandi; S., Salprima Yudha; Banon, Charles; Oktiarni, Dwita; Adfa, Morina (Faculty of Pharmacy, Universitas Pancasila, 2023)
The purpose of this study was to look into the antibacterial activity of methanolic extract of Excoecaria cochinchinensis as well as the effect of its combination with antibiotics on the growth of Klebsiella pneumoniae, Enterobacter aerogenes, and Staphylococcus epidermidis. The antibacterial activity test was carried out using the well diffusion method, and the combined effect of the extract and antibiotics was observed using the paper strip diffusion method. At various concentrations (25, 50, 75, 100, 150, 200, and 250 mg/mL), the extract significantly inhibited the growth of K. pneumoniae, E. aerogenes, and S. epidermidis. The inhibitory zone's diameter increased proportionally with the extract concentration. The growth of K. pneumoniae and S. epidermidis was then classified as extremely sensitive (+++) to the addition of the extract at 200 and 250 mg/mL concentrations, meanwhile, E. aerogenes’s with 250 mg/mL of the extract. Secondary metabolites such as oleanolic acid, arjunolic acid, scopoletin, kaempferol, quercetin, diterpenoid compounds, tannins, and other phenolics have been reported from E. cochinchinensis leaves and are thought to be responsible for its antimicrobial activity. The effect of the extract’s combination with antibiotics was insignificant compared to their individual activity, thereby classifying them as indifferent.